2015
DOI: 10.1007/s10763-015-9653-2
|View full text |Cite
|
Sign up to set email alerts
|

Explaining Student Achievement: the Influence of Teachers’ Pedagogical Content Knowledge in Statistics

Abstract: Abstract:Statistics is an increasingly important component of the mathematics curriculum. StatSmart was a project intended to influence middle-years students' learning outcomes in statistics through the provision of appropriate professional learning opportunities and technology to teachers. Participating students in Grade 5/6 to Grade 9 undertook three tests, a pre-test, a post-test and a longitudinal retention test over a period of two years. Their teachers completed a survey that included items measuring ped… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 35 publications
1
13
0
4
Order By: Relevance
“…The application of PCK in the learning process is important because it can make it easier for students to understand biological content. The teacher's PCK can influence the way of learning and student learning outcomes [11,12].…”
Section: Discussionmentioning
confidence: 99%
“…The application of PCK in the learning process is important because it can make it easier for students to understand biological content. The teacher's PCK can influence the way of learning and student learning outcomes [11,12].…”
Section: Discussionmentioning
confidence: 99%
“…Jadi guru adalah orang yang penting dalam menentukan kejayaan suatu pembaharuan pendidikan (Ma 2010;Nuraini & Leong 2010;Umi Nadiha et al 2016). Walaupun banyak kajian membuktikan pendekatan pengajaran yang berkesan adalah berpusatkan murid, guru masih selesa menggunakan kaedah konvensional yang berpusatkan guru (Callingham et al 2016;Hashweh 2016). opsyen Guru Matematik Sekolah Rendah sebagai Moderator dalam Hubungan Berstruktur Dalam latihan praperkhidmatan, guru pelatih membuat pilihan pengkhususan iaitu 'opsyen,' sekurang-kurangnya dalam satu mata pelajaran.…”
Section: Pengenalanunclassified
“…Teachers must have good conceptions when teaching on the class [4]. Teacher who do a mistake on teaching show negatif impact for students' achievement [5]. However, many studies found that many teachers have mistaken on any concepts [6].…”
Section: Introductionmentioning
confidence: 99%